Effect of Flow Attack Angle of V-Ribs Vortex Generators in a Square Duct on Flow Structure, Heat Transfer, and Performance Improvement. (2nd February 2014) - Boonloi, Amnart
Abstract : A numerical investigation has been carried out to examine the periodic laminar flow and heat transfer characteristics in a three-dimensional isothermal wall square duct with 20° inline V-ribs. The computations are based on the finite volume method, and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the hydraulic diameter of the square duct ranging from 100 to 2000. To generate main streamwise vortex flows through the tested section, V-ribs with an attack angle of 20° are mounted in tandem with inline arrangement, pointing downstream (V-Downstream) and pointing upstream (V-Upstream) placed on both the upper and lower walls. Effects of different blockage ratio (b / H, BR) with a single pitch ratio (P / H, PR) of 1 on heat transfer, pressure loss, and performance in the ribbed tube are studied. Apparently in each of the main vortex flows, streamwise twisted vortex flows can induce impinging flows on the walls of the interbaffle cavity leading to drastic increase in heat transfer rate over the square duct. In addition, the rise in the V-baffle height results in the increase in the Nusselt number and friction factor values. The computational results show that the optimum thermal enhancement factor is about 4.2 atBR = 0.20 and 0.15 for the V-Downstream and V-Upstream, respectively.